Point-of-care ultrasound in early diagnosis and monitoring of deep abscess in newborns: a case report of two cases - Du, Bang; Xu, Fengdan; Deng, Biying; Zhong, Baimao; Li, Ning; He, Xiaoguang (Frontiers in Pediatrics, 2024)
Objective: This study sought to analyze the value of point of care ultrasound (POCUS) in early diagnosis and monitoring of deep abscess in newborns. Methods: Retrospective analysis of the clinical data of two newborns admitted to the Neonatal Intensive Care Unit (NICU) of our hospital and diagnosed with deep abscess of the newborn. Combined with literature analysis, the value of POCUS in early diagnosis and monitoring of deep abscess of the newborn was evaluated.The two newborns reported in this article were all admitted to NICU due to "fever". POCUS was used to assist in early diagnosis of "liver abscess" and "lung abscess". Subsequently, POCUS was used to monitor lesion changes and adjust treatment plans. All patients were cured and discharged with a good prognosis. Conclusions: Deep abscesses in newborns are very rare and often life-threatening, but apart from fever, they often have no specific clinical manifestations and are easily misdiagnosed or missed. POCUS, as a bedside auxiliary examination tool, has high accuracy, radiation free, non-invasive, and convenient, and has high diagnostic and monitoring value in early diagnosis and monitoring of deep abscess in newborns.